Development of L2 disciplinary literacy: A multidimensional analysis. (November 2022) - Qiu, Xuyan; Lo, Yuen Yi; Teng, Xing San
Abstract: Bilingual education programmes have become popular worldwide in part because they are believed to facilitate second/foreign/additional language (L2) learning, often with English as the target L2. In such programmes, students learn content and L2 simultaneously, but a common difficulty they encounter is mastering disciplinary literacy in the L2. However, research exploring bilingual students' development of L2 disciplinary literacy remains scarce. Therefore, this paper analyses a corpus of biology examination essays produced by a stratified sample of students studying in English medium education (EMI) in Hong Kong (204 essays totalling 45, 823 words) using Multidimensional Analysis Tagger (Nini, 2015). The multidimensional analysis shows that this sample generally produced texts containing features closely related to scientific exposition. This paper also compares the features of essays written by students at different levels of academic performance as measured by their examination scores. The results show that the essays produced by students with better scores were more similar to academic prose, consisted of denser and more abstract information and used more academic vocabulary, nominalisation, conjunctions, and passive voice. This study demonstrates a potential relationship between students' mastery of disciplinary literacy and their academic achievement, thereby having implications for pedagogy in bilingual education programmes.